Arterial hypertension associated with renal failure in Latin America: systematic review - Palma, Andrés S.; Zamora, Elisa L.; García, Jared F.; Zamora, Karla R.; Contreras, Denise I.; Domínguez, Maritza R. (Revista Gregoriana de Ciencias de la Salud, 2024)
The relationship between arterial hypertension (AHT) and chronic renal failure (CRF) is based on the fact that the parameters of albuminuria due to renal failure are associated with an increased risk of suffering cardiovascular events due to the consequent renal damage caused by AHT. The aim of this article is to explain the relationship between the lifestyles of the inhabitants of Latin America as an underlying cause of AHT and CRF, using bibliographic search sources such as Google Scholar to investigate studies carried out in the region. The search showed studies that portray the interrelationship between AHT and chronic renal disease (CRD), so that CRD can progress to CRF, together with lifestyle and AHT, for this reason, promotion and prevention are essential for the control of these pathologies.